Tinjauan Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja (SMK3) (Studi Kasus: Pembangunan Gedung Living World Pekanbaru) - Pesa, Fitri Amalia; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pekanbaru is the capital city of the Riau province where it’s heading to metropolis, so development both hospitals, hotels and shopping malls city are growth rapidly. The construction of the Living World Pekanbaru, located in Soekarno-Hatta street, by lifting the concept of lifestyle center. This project has a number of employees more than 400 people, and the number of works that is four times larger than minimum the government regulations which increased the risk of workplace accidents. In order to reduce this risk, it is necessary implemented SMK3 in the project. The research method is using quantitative method and then the univariate analysis descriptive method and qualitative method. Questionnaire was taken from 400 workers and 27 staff of the projects with reference to Government Rule number 50 of 2012. As a result, The implementation SMK3 reached 71,49% included in the category GOOD. SMK3 audit assessment for building project Living World Pekanbaru has reached 94 % and is at SATISFY category. Audit SMK3 which produces 3 criteria do not correspond minor and 6 major criteria for inappropriate. The Calculation of cost analysis tools and equipment procurement project K3 is equal to Rp.88.009.203,00 or 0,0002% of the entire value of the project contract. In addition, the implementation SMK3 have an inhibiting factor such as tiring, sleepless and work pressure from management.Keywords: Living World Pekanbaru, Risk, SMK3, Audit, Inhibiting factor